Notas sobre la justificación sintáctica de la variatio - Hernández Cabrera, Tomás (1997)
The aim of this paper is to discuss whether the so-called variatio is really a rethorical image. From the commentary of a few passages from Classical Latin it is concluded that this image of speech is a result of the linguistic use instead of the authors' will.
Keywords: Sintaxis; Lengua latina